New strategy for controlling root-knot nematodes: research on the resistance of tobacco grafting progenies to root-knot nematodes - Li, Qiankun; Xu, Xingyang; Yao, Hanyang; Li, Yunxia; Ning, Dekai; Tian, Jijuan; Hu, Xianqi; Yang, Yanmei (Frontiers in Plant Science, 2025)
IntroductionTo explore the changes in agronomic traits, differences in disease resistance, and related enzymatic mechanisms of tobacco grafted progeny after inoculation with root-knot nematodes (RKNs), and to elucidate their defense responses.MethodsWe used the F1 progeny of tobacco grafts ‘Banqiao B (moderately resistant rootstock) + Honghua Dajinyuan (susceptible scion)’ (BHF1) and ‘G278 (resistant rootstock)+ Honghua Dajinyuan’ (GHF1) as experimental materials, with the scion variety Honghua Dajinyuan (HD) as the control. We conducted a systematic comparison of agronomic traits, disease resistance, and enzymatic characteristics among the materials 90 days post-inoculation with RKNs.Results and discussionAgronomic traits did not differ significantly between the grafted progeny and HD. The disease index (DI) of HD and BHF1 was 74.07, indicating susceptibility (S), while GHF1 exhibited a DI of 22.22, indicating moderate resistance (MR). The Soil and Plant Analyzer Development (SPAD) value of GHF1 was significantly higher than that in HD and BHF1. Although superoxide dismutase (SOD) and catalase (CAT) activities in the leaves and roots of GHF1 were comparable to those in HD, the activities of peroxidase (POD), phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), chitinase (CHT), and β-1,3-glucanase (GLU) in the roots were significantly elevated compared to those in the other treatments. Correlation analysis revealed significant negative correlations between the DI and both the SPAD value and the activities of POD, PAL, PPO, CHT, and GLU, suggesting that increased chlorophyll content and enhanced defense-related enzyme activities contributed to the improved resistance of GHF1. GHF1 thus constitutes a valuable germplasm for nematode resistance. These findings provide a foundation for the selection, propagation, and characterization of grafted tobacco progeny and offer new strategies for breeding tobacco cultivars resistant to RKNs.